Effect of Exercise Method and Eye-Foot Coordination on Passing Accuracy Ps. UIR - Alficandra Alficandra; Raffly Henjilito; M. Fransazeli Makorohim Makorohim (STKIP Muhammadiyah Kuningan, 2022)
This study aimed to analyze the training method of passing target fixed target eye-foot coordination high-low and target passing moving eye-foot coordination high-low and to analyze the interaction between passing training methods and eye-foot coordination on soccer passing accuracy. This study used a quasi-experimental pre-test and post-test design method. The population in this study amounted to 36 players. The sampling technique used total sampling with a sample of 36 players and data analysis using the ANOVA test. The results of study 1) There is a difference in the effect between fixed target and moving-to-target passing exercises on soccer passing accuracy. 2) There is a different effect between high and low eye-foot coordination on passing accuracy. 3) There is a difference in the effect of the Fixed Target Passing Practice Method with High and Low Eye-foot Coordination on the Accuracy of Football Passing. 4). There is a difference in the effect of moving target passing exercises with high and low eye-foot coordination on soccer passing accuracy. 5) There is no interaction between training methods and eye-foot coordination on soccer passing accuracy. The study's conclusion shows that moving target passing exercises are better at increasing passing accuracy than fixed target passing exercises, and players with high eye-foot coordination have better accuracy than players with low eye-foot coordination.